Early-life hyperoxia-induced Flt3L drives neonatal lung dendritic cell expansion and proinflammatory responses - Cui, Tracy X.; Brady, Alexander E.; Zhang, Ying-Jian; Fulton, Christina T.; Goldsmith, Adam M.; Popova, Antonia P. (Frontiers in Immunology, 2023)
Premature infants with chronic lung disease, bronchopulmonary dysplasia (BPD), develop recurrent cough and wheezing following respiratory viral infections. The mechanisms driving the chronic respiratory symptoms are ill-defined. We have shown that hyperoxic exposure of neonatal mice (a model of BPD) increases the activated lung CD103+ dendritic cells (DCs) and these DCs are required for exaggerated proinflammatory responses to rhinovirus (RV) infection. Since CD103+ DC are essential for specific antiviral responses and their development depends on the growth factor Flt3L, we hypothesized that early-life hyperoxia stimulates Flt3L expression leading to expansion and activation of lung CD103+ DCs and this mediates inflammation. We found that hyperoxia numerically increased and induced proinflammatory transcriptional signatures in neonatal lung CD103+ DCs, as well as CD11bhi DCs. Hyperoxia also increased Flt3L expression. Anti-Flt3L antibody blocked CD103+ DC development in normoxic and hyperoxic conditions, and while it did not affect the baseline number of CD11bhi DCs, it neutralized the effect of hyperoxia on these cells. Anti-Flt3L also inhibited hyperoxia-induced proinflammatory responses to RV. In tracheal aspirates from preterm infants mechanically-ventilated for respiratory distress in the first week of life levels of FLT3L, IL-12p40, IL-12p70 and IFN- were higher in infants who went on to develop BPD and FLT3L levels positively correlated with proinflammatory cytokines levels. This work highlights the priming effect of early-life hyperoxia on lung DC development and function and the contribution of Flt3L in driving these effects.